2003
DOI: 10.1364/ao.42.006838
|View full text |Cite
|
Sign up to set email alerts
|

Design and assessment of microlenslet-array relay optics

Abstract: Recent progress in micro-optics fabrication and optical modeling software opens the opportunity to investigate how microlenslet-array-based compact relay systems can be designed and assessed. We present various optical configurations that include an appropriate baffle computation to eliminate ghost images, followed by an analysis of image quality. The investigation shows the existing trade-off between compactness of the system and a tiling effect observed in the corresponding image, an effect we refer to as le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In contrast to highly symmetric relaying array optics [151,157] such instances occur very rarely in the CLEY, because the pitches of the different microlens-and aperture arrays have no rational relation. However, the lateral repeating of the superstructure of the Gabor superlens and consequently spurious light are a natural property of this arrangement of MLAs (see Section 2.2).…”
Section: H Non-sequential Raytracing Analysis Of Cleymentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to highly symmetric relaying array optics [151,157] such instances occur very rarely in the CLEY, because the pitches of the different microlens-and aperture arrays have no rational relation. However, the lateral repeating of the superstructure of the Gabor superlens and consequently spurious light are a natural property of this arrangement of MLAs (see Section 2.2).…”
Section: H Non-sequential Raytracing Analysis Of Cleymentioning
confidence: 98%
“…A close-up imaging of documents, displays and intermediate images ("relay optics") with refractive microlens- [150] or telescope arrays having a unity magnification [66,67,[151][152][153][154], variable magnification using Alvarez lenses [155] or small demagnification [156,157] was proposed, theoretically analyzed or experimentally demonstrated.…”
Section: State Of the Art Of Man-made Vision Systemsmentioning
confidence: 99%
“…10 The imaging capabilities of microlenslet arrays for either grayscale or color images were previously investigated, and it was demonstrated that 1:1 compact relays for such images could be conceived with OAL of less than 7mm. 11 The two key challenges when imaging with multi-aperture stacks of microlenslet arrays are the formation of ghost images in the system and lensletization. 11 The formation of ghost images in a multi-aperture imaging system comprising of a stack of microlenslet arrays is caused by the light emitted from the object in all directions taking more than one optical path through the system.…”
Section: Key Challenges In Imaging With Microlenslet Arraysmentioning
confidence: 99%
“…In addition, enough overlap among the sub-fields of view of each microlenslet pair was secured to minimize the lensletization. 9 The final optical layout of the investigated system is shown in Fig. 3 …”
Section: Optical Layout Of Microlenslet-array Based Magnifying Systemmentioning
confidence: 99%
“…In the case of grayscale images, image quality may be assessed subjectively as well as with more sophisticated quantitative approaches. 9 The optical layout of a 1:2 system using two arrays of each 9 by 9 microlenses, combined with an associated baffle located at the entrance pupil of the system is shown in Fig 4. Moreover, each lens in the first array was an F/5 square plano-convex lens, of 0.15mm thickness, and 500µm focal length. Each lens in the second array was an F/8.3 square plano-convex lens, of 0.15mm thickness, and 1000µm focal length.…”
Section: Theoretical Modelingmentioning
confidence: 99%